EVALUASI KINERJA STRUKTUR BANGUNAN GEDUNG TAHAN GEMPA DENGAN METODE ANALISIS RESPONS SPEKTRUM DAN TIME HISTORY - Muhammad Irsan Arrasyid; Istiqomah Istiqomah; Ben Novarro Batubara; Budi Kudwadi (Universitas Pendidikan Indonesia (UPI), 2023)
The city of Bandung is one of the cities that is prone to earthquakes because it is passed by the Lembang fault. Therefore, buildings in the city of Bandung should have implemented the concept of earthquake-resistant buildings in their construction. To avoid the occurrence of damage or collapse of the structure of the building against an earthquake, it is necessary to analyze the building against the earthquake. This study aims to determine how many deviations occur in the building due to the earthquake and the performance of the building structure. The method used is the response spectrum and time history analysis method and then evaluates the performance of the structure against earthquakes using the ATC-40 standard. The building that is the case study is the Directorate of Drugs and the Directorate of Intelligence and Security for the West Java Police, which consists of 5 floors. Structural modeling and analysis were performed using ETABS v20. Earthquake records used are Imperial Valley, Kobe and Trinidad earthquakes. Based on the results of the analysis of the maximum deviation with the response spectrum method 26.74 mm in the X direction and 26.46 mm in the Y direction. Meanwhile, for the time history analysis, it was obtained 33.05 mm in the X direction and 28.96 in the Y direction. The maximum value of the total deviation obtained 0.0016 m and the maximum value of inelastic deviation obtained 0.0014 m so that it shows the level of performance of this building structure based on ATC-40 is Immediate Occupancy (IO), which means the structure is in a safe condition.Keywords : ATC-40, earthquake resistant buildings, spectrum response, time history,